Emotional Minds The Passions and the Limits of Pure Inquiry in Early Modern Philosophy - Ebbersmeyer, Sabrina (De Gruyter, 2012)
The thoroughly contemporary question of the relationship between emotion and reason was debated with such complexity by the philosophers of the 17th century that their concepts remain a source of inspiration for today`s research about the emotionality of the mind. The analyses of the works of Descartes, Spinoza, Leibniz, and many other thinkers collected in this volume offer new insights into the diversity and significance of philosophical reflections about emotions during the early modern era. A focus is placed on affective components in learning processes and the boundaries between emotions and reason.